bahasa inggris - Muhammad Faruq hanafi; Sarafuddin Sarafuddin (UNIVERSITAS SLAMET RIYADI, 2023)
Learning and tahfidz Al-Qur'an is now becoming a good trend among Muslims today. Methods for memorizing the quran for elementary school children are very diverse, but in reality there are still many methods that are not quite right so that children get bored quickly and tend to get bored easily. Recently, several well-known tahfidz methods have appeared for elementary school children, namely the talaqi, tawazun, tabarak, and Zahrawain methods. Undoubtedly, the main path for the revival of Muslims is to return to the Quran. So it is necessary to have At-Takbir At-Tajdid (early regeneration) to give birth to a golden generation of Muslims who excel in memorizing the Al-Quran. Memorizing the Al-Quran with various methods does not wait for the child to be good at reading the Al-Quran first. Children who do not know hijaiyah letters can use existing methods to memorize elementary school children. This research focuses on the tahfidz learning method for elementary school children. The purpose of this study is to find out the implementation of the talaqi, tawazun, tabarak, and zahrawain methods. The research method used in this research is descriptive qualitative. The approach used in research on the implementation of these methods for elementary school children is a phenomenological approach by approaching existing social phenomena. In this study, the comparison of the tahfidz method is the subject. The source of this research is literature reviewed. Researchers act in collecting and analyzing data, this research is more on process than results, there are limits to the problems found in the focus of research, and also data analysis tends to be inductive. Data collection techniques using literature review. In qualitative research, data analysis is carried out during and after data collection. Data is analyzed in the form of words, sentences, narratives that are descriptive in nature. The application of descriptive analysis techniques is carried out in three ways, namely: data reduction, data presentation, and withdrawal. From the results of the research conducted, it was concluded that the zahrawain method is the most appropriate method for learning the Quran and perfecting the talaqi, tawazun, or tabarak methods. Although there are still several supporting and inhibiting factors.